Accumulation and Release of Mercury in the Lichen Evernia prunastri (L.) Ach - Andrea Vannini (MDPI AG, 2021)
This study investigated the dynamics of the accumulation and release of Hg2+ in lichens, using Evernia prunastri (L.) Ach. as a model species. Thalli were incubated with solutions containing 1, 10, and 100 µM Hg2+ and then exposed for 1, 2, 3, 6, 12, 18, and 24 months at the Botanical Garden of the University of Siena (a location free from local Hg sources). Lichen samples accumulated Hg proportionally to the exposure concentration, and after the exposure, reductions over time were evident, already starting from 1–2 months. After 24 months, samples released 72–74 (healthy thalli) to 94% (unhealthy thalli) of the accumulated Hg, but control values of untreated samples were never reached. Depending on the Hg content after the exposure, stable decreased concentrations were reached after 6–24 months. The results of this study highlight the ability of the lichen E. prunastri to reflect rapidly increasing environmental Hg concentrations, as well as to indicate an ameliorated situation (e.g., the closure of an Hg source). However, we have found evidence that an acute pollution episode can influence the content of Hg in lichens for several years.